Social media- an effective tool to influence purchase decisions of students- a case study at a public Higher Education Institution in South Africa - Fathima Khan-Ameer; Dr. Marlini Moodley (The Retail and Marketing Review)
Social media platforms provide companies with vast consumer markets, where students openly share their preferences and opinions, allowing marketers to observe and even guide their choices. As social media content spreads rapidly, it fosters conformity in consumer behaviour, with students often influenced by the opinions and feedback of their peers and online communities. The aim of this study is to understand the extent to which social media influences the way in which students make purchasing decisions. While significant research has examined consumer decision-making, the specific impact of social media remains underexplored. Therefore, this study investigates the influence of social media on student purchasing behaviour, highlighting how social networks shape consumer attitudes and decisions among students. A quantitative research approach was employed, using a structured survey administered to 380 students from five campuses of Institution X- a public Higher Education Institution. The survey examined demographics and social media interactions, with data analysed using IBM SPSS Version 22. Findings revealed that online discussions and user feedback significantly influence students’ purchasing decisions. A significant number of respondents expressed trust in user-generated content on social media, such as reviews, recommendations, and personal experiences shared by other users. The study concludes that social media plays a critical role in shaping student consumption behaviour, providing a powerful platform for retail businesses to engage with young consumers. Students frequently rely on online reviews and peer opinions to inform their choices, underscoring the importance for brands to actively manage their social media presence.